Blockchain-based micropayment system for secured cashless small payments - Siam, Morshed; Mandal, Shovon; Keya, Mahmuda Akter; Dhar, Swarojani; Tahsin, H.M. Irfan (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.